2017
DOI: 10.1111/jcal.12194
|View full text |Cite
|
Sign up to set email alerts
|

Improving mastery of fractions by blending video games into the Math classroom

Abstract: Concepts from the Australian mathematics curriculum on fractions were used as core elements to design three computer games. In each game, the concepts were presented in the form of tangible puzzles, customized to a difficulty level based on student capability. The games were integrated into a single virtual game world, and a fantasy story was used to help build a compelling experience. Five Year 6 classes were used to evaluate the game over four weeks. Three of the classes were provided with the games, and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In this sense, mobile-based applications are a very important material in the sense of the efficiency of the learning environment. A study by Masek et al (2017) found that the experiment group with access to games in addition to direct teaching received higher points compared to control group students. When students with lower levels of fraction skills are examined especially, students with access to games appeared to have larger developments in skills.…”
Section: Mobile Learning (The Use Of Game-based App In Education)mentioning
confidence: 99%
“…In this sense, mobile-based applications are a very important material in the sense of the efficiency of the learning environment. A study by Masek et al (2017) found that the experiment group with access to games in addition to direct teaching received higher points compared to control group students. When students with lower levels of fraction skills are examined especially, students with access to games appeared to have larger developments in skills.…”
Section: Mobile Learning (The Use Of Game-based App In Education)mentioning
confidence: 99%
“…Motion math (Riconscente, 2013) and Semideus (Kiili et al, 2018) are designed based on the measurement interpretation of fractions and relied on fraction number lines. Finally, Abydos (Masek et al, 2017) includes high‐level fraction concepts such as equivalent fractions, identifying least common multiples, addition, and subtraction of fractions.…”
Section: Dgbl and Fraction Learningmentioning
confidence: 99%
“…Finally, studies have not always used an exhaustive, standardized, or country‐based assessment to test for fraction skills (Kiili et al, 2018; Martin et al, 2015). The studies that did use fraction test items from standardized assessments also vary in their selection of the test items, raising the possibility that the results are dependent upon that selection (Masek et al, 2017; Riconscente, 2013). This highlights the need for pre‐registering hypotheses and methods when assessing the impact of an intervention (Bertram, 2020; Nosek et al, 2018).…”
Section: Dgbl and Fraction Learningmentioning
confidence: 99%
“…In recent years, studies examining the effects of digital game-based learning environments on players' rational number competencies have yielded positive results. For example, games have been shown to support students' understanding of fraction equivalence and comparison, number line estimation, arithmetic skills, and attitudes towards fraction learning (Gresalfi et al, 2018;Masek et al, 2017;Nejem & Muhanna, 2013;Riconscente, 2013). Further, the affordances and efficiencies provided by properly designed digital games may improve students' engagement and motivation and enhance their conceptual understanding of rational numbers (Zhang et al, 2020).…”
Section: Digital Game-based Learning Environments For Rational Number Learningmentioning
confidence: 99%